Development of Ethnomathematics-Based Educational Game Media to Improve Metacognitive Abilities and Learning Motivation in the Material of Flat Area of Grade V Elementary School - Andari, Sabina; I Made Suarjana; I Nyoman Laba Jayanta (MIMBAR PGSD Undiksha, 2024)
This development research is motivated by the suboptimal use of media models and learning strategies in elementary schools, as well as the low metacognitive abilities and learning motivation of fifth-grade students. The aim of this study is to analyze the prototype, validity, practicality, and effectiveness of the developed media in improving metacognitive skills and learning motivation of Grade V elementary school students. The research was conducted using the ADDIE development model. The subjects of the study were 4 experts and 42 students. The product developed in this study is an ethnomathematics-based educational game media for Grade V elementary school students. Data collection methods included observation, document study, questionnaires, and interviews. In this study, data were collected using questionnaires and tests. The data analysis techniques used were descriptive and inferential analysis. The development research showed high validity, with both media and content experts giving an average score of 0.94. Students rated the practicality at 86%, indicating it is well received. The results of the correlated sample t-test on learning motivation showed a significance value of 0.000, which is less than 0.05. Therefore, H0 is rejected and H1 is accepted. It can be concluded that the development of this ethnomathematics-based educational game is feasible, practical, and effective in enhancing the metacognitive knowledge and learning motivation of Grade V students. The latest findings from this study imply that it can serve as a reference for developing more innovative learning activities.